Africa's Pulse, No. 25, April 2022 - Zeufack, Albert G. (Washington, DC: World Bank, 2022)
Sub-Saharan Africa's recovery from the pandemic is expected to decelerate in 2022 amid a slowdown in global economic activity, continued supply constraints, outbreaks of new coronavirus variants, climatic shocks, high inflation, and rising financial risks due to high and increasingly vulnerable debt levels. The war in Ukraine has exacerbated the already existing tensions and vulnerabilities affecting the continent. Given the sources of growth in the region and the nature of the economic linkages with Russia and Ukraine, the war in Ukraine might have a marginal impact on economic growth and on overall poverty—as this shock affects mostly the urban poor and vulnerable people living just above the poverty line. However, its largest impact is on the increasing likelihood of civil strife as a result of food- and energy-fueled inflation amid an environment of heightened political instability. The looming threats of stagflation require a two-pronged strategy that combines short-term measures to contain inflationary pressures and medium-to-long-term policies that accelerate the structural transformation and create more and better jobs. In response to supply shocks, monetary policy in the region may prove ineffective to bring down inflation and other short-run options may be restricted by the lack of fiscal space. Concessional financing might be key to helping countries alleviate the impact of food and fuel inflation. Over the medium term, avoiding stagflation may require a combination of actionable measures that improve the resilience of the economy by shoring up productivity and job creation. Lastly, ongoing actions to enhance social protection—including dynamic delivery systems for rapid scalability and shock-sensitive financing—could be strengthened further to improve economic resilience against shocks and foster investments in productive assets.